Integrated assessment of the tourist-recreational potential in the aktobe oblast (ҚазҰУ Хабаршысы. География сериясы, 2021)
Assessment of the tourist-recreational potential of the Aktobe oblast is the main tool for determining the prospects for its development and strategic planning. The article presents the methodology and results of assessing the potential of tourist and recreational development of the Aktobe oblast. The integrated assessment of the tourist-recreational potential in the Aktobe oblast includes a criteria basis for evaluating three groups of tourism development resources: natural and climatic, historical and cultural, and socio-economic. Taking into account the lack of statistical indicators, the article analyzes the potential of tourism in the districts of Aktobe oblast on the basis of evaluation criteria selected using the General balance method. The tourist-recreational potential of natural and cultural resources of the Aktobe oblast has features that affect the development of the territorial organization of tourism. The objects of cultural and historical heritage that have been preserved to date reflect the identity of the Aktobe oblast. A thorough analysis of the results of the assessment of tourist and recreational activities of the oblast, competent work and investment give an idea of the territories where new tourist facilities may appear. As a result of the analysis, it turned out that these resources are located unevenly, and a high level of tourism development in the context of natural and climatic resources of the oblast is revealed in the service of tourists. The results of the analysis can be used to solve organizational and managerial tasks for the balanced development of tourism at the oblastal and local levels.